Hubungan Kompetensi Komunikasi dan Fasilitas Belajar dengan Motivasi Belajar Mahasiswa - Nadia Adela; Ernita Arif; Aidinil Zetra (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2021)
Abstract:This research is an explanative study which aims to answer the question of why and how the social phenomena or phenomena in question, in this case learning motivation can occur, by explaining the effect of variable X on variable Y. The results of the hypothesis test obtained using SPSS 17.0 show that the coefficient of determination (R Square) is 0.947 or equal to 94.7%. This figure implies that the communication competence variable (X1) and the learning facility variable (X2) simultaneously affect the learning motivation variable (Y) by 94.7%, while the rest is influenced by other variables outside this regression equation.